THE RELATION OF THE SPLEEN TO BLOOD DESTRUCTION AND REGENERATION AND TO HEMOLYTIC JAUNDICE : VII. THE EFFECT OF HEMOLYTIC SERUM IN SPLENECTOMIZED DOGS. - Pearce, Richard M. (The Rockefeller University Press, 1913)
The increased resistance of the red blood corpuscles characteristic of the splenectomized animal is as evident one year after removal of the spleen as it is at earlier periods. So also is the decreased tendency to jaundice after the administration of hemolytic serum. The increase in resistance of the red cells cannot be explained on the basis of an increase in reticulated cells in the circulating blood.